Hiding patients’ medical reports using an enhanced wavelet steganography algorithm in DICOM images - Mostafa A. Ahmad (Alexandria Engineering Journal, 2022)
In the latest years, there is an increasing emphasis on DICOM medical images, especially in digital medical images transmission to e-health services. Besides, the confidentiality and protection of patients’ secure information need more attention and research. In this paper, we propose an enhanced medical image steganographic algorithm to hide patients’ secure information in their medical images. The proposed algorithm has a higher level of confidentiality while maintaining a higher quality of the medical image and a higher embedding capacity and robustness. The proposed algorithm has two main steps. The medical cover image is decomposed using an integer wavelet filter in the first step. Moreover, the patients’ confidential information is processed using the Arithmetic Coding (AC) and Data Encryption Standard (DES) algorithms to be compressed and encrypted before of the embedding process. In the second step, the insignificant coefficients are selected from the integer wavelet high-frequency subbands of the transformed medical image, and finally, both the target cover bits and the secret bits are grouped during the injection process. The performance of our algorithm was evaluated using different evaluation metrics. The obtained results show that our algorithm outperforms existing ones, with a higher embedding capacity, and a lower imperceptibility. The proposed algorithm can be applied in hospitals and health care canters worldwide.